ダイ50ジ ナンキョク チイキ カンソクタイ カキ コウドウ ホウコク 2008-2009 - 小達, 恒夫; オダテ, ツネオ; 石沢, 賢二; イシザワ, ケンジ; Odate, Tsuneo; Ishizawa, Kenji (2010)
P(論文) 第50次南極地域観測隊夏期行動の概要を報告する.第50次隊は総勢46名で構成され,このうち越冬隊は28名,夏隊は18名であった.他に夏隊同行者として,1名が参加した.昭和基地方面で夏期行動を展開した第50次観測隊本隊は,オーストラリアの観測船「オーロラ・オーストラリス」を活用した.観測隊本隊は12月25日に航空機で出発し,西オーストラリアのフリーマントルで「オーロラ・オーストラリス」に乗船した.「オーロラ・オーストラリス」は12月30日に同地を出港し,海洋観測を実施しつつ1月12日に氷縁に到着した.1月13日に昭和基地第1便が飛び,2009年2月2日の最終便までの間に,第50次越冬隊成立に必要な物資(91.8トン)の輸送と越冬隊員の交代を完了した.この期間の観測計画では,「オーロラ・オーストラリス」船上において氷海内の海洋観測を実施した.昭和基地における設営計画では,「しらせ」後継船就航に伴う輸送システムの整備として,道路整備工事,ヘリポート待機小屋建設等を実施した.往復の航路上では,海洋観測を実施し,ホバートに2月20日に到着,観測隊は航空機で2月24日に帰国した.一方,航空機により南極へ入りセール・ロンダーネ山地へ向かった隊は11月16日に成田を出発し,DROMLANチャーター機により,11月23日,プリンセスエリザベス基地(ベルギー)に到着した.同隊は,セール・ロンダーネ山地の西部で野外調査を実施した後,2月11日にケープタウンに戻り,2月17日に成田空港へ到着した. The activities in the 2008-2009 austral summer of the 50th Japanese Antarctic Research Expedition (JARE-50) are reported. JARE-50 consisted of 46 personnel including 18 summer personnel and 28 wintering personnel. In addition, one observer joined the voyage to the Syowa Station. The voyage and summer operation arround Syowa Station were supported by staff from Australian Antarctic Division using the Icebreaker Aurora Australis. Expeditioners for Syowa Station (28 wintering personnel, 12 summer personnel and one observer) departed on 25 December and were on board Aurora Australis at Fremantle, Western Australia. She departed for Syowa Station on 30 December and arrived at the ice edge in Lu¨tzow-Holm Bay on 12 January. The first helicopter from Aurora Australis landed at Syowa Station on 13 January. Transport of cargo (91.8 tons) and exchange of wintering personnel were completed by 2 February. During the stay in Lu¨tzow-Holm Bay, oceanographic observation was conducted in the sea ice area from Aurora Australis as well as several summer construction plans for the new unloading system from JARE-52 performed by the new Icebreaker Shirase. The JARE-50 summer party and JARE-49 wintering party on board Aurora Australis left Syowa Station on 2 February. On the return voyage, oceanographic and marine biological observations were carried out. All personnel disembarked at the ...